The correlation between multiple HPV infections and the occurrence, development, and prognosis of cervical cancer - Na, Jing; Li, Ya; Wang, Jun; Wang, Xinyou; Lu, JunLing; Han, Shichao (Frontiers in Microbiology, 2023)
Cervical carcinoma is the fourth female malignant tumor in the world, and the persistent infection of high-risk human papillomavirus (HPV) is recognized as the most common cause. This article studies the correlation between multiple HPV infections and the occurrence, development, and prognosis of cervical cancer in order to provide more references for clinical diagnosis and treatment. We conducted a retrospective analysis of the clinical data of 400 cervical carcinoma patients admitted to our hospital from 2015 to 2023. The collected patient data include age, HPV infection status, tumor size and morphology, local infiltration depth, diagnostic staging, surgical approach, vascular cancer thrombus status, lymph node status, and postoperative HPV follow-up status. We use SPSS statistical software for data analysis. Our research shows that the high-risk age group for cervical carcinoma is concentrated between 41 and 60 years old, which is basically consistent with the age range of the high incidence of HPV infection. In the statistics for HPV infection types, ~67.7% of patients are single HPV-infected, 25.29% are double infected, and 7.00% are infected with three or more types of HPV. Among the multiple HPV infections, most of the patients are younger than 40 years old and older than 70 years old, with double infection accounting for the majority. The top five HPV subtypes with high detection rates belong to high-risk subtypes, which are the HPV16, 18, 58, 33, and 52 subtypes, respectively. There was no significant relationship between multiple HPV infections and cervical cancer stage, lesion size, pathological tissue type, tissue differentiation degree/vascular cancer thrombus, and lymph node metastasis, and there was no significant difference in the results between the groups. In summary, multiple types of HPV infection in the cervix are common. We found that multiple infections, mainly HPV16, are closely related to cervical cancer. For the HPV16, 18, 58, 33, and 52 subtypes of infection, especially for patients younger than 40 years old and older than 70 years old, priority should be given to prevention and treatment. The relationship between multiple HPV infections and the progression and prognosis of cervical carcinoma requires further research, which could better guide cancer prevention and treatment.